Combined intervention with pioglitazone and n-3 fatty acids in metformin-treated type 2 diabetic patients: improvement of lipid metabolism - Veleba, Jiří; Kopecký, Jan; Janovská, Petra; Kuda, Ondřej; Horáková, Olga; Malínská, Hana; Kazdová, Ludmila; Oliyarnyk, Olena; Škop, Vojtěch; Trnovská, Jaroslava; Hájek, Milan; Škoch, Antonín; et al. (Nutrition & metabolism, 2015)
BACKGROUND: The marine n-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) exert numerous beneficial effects on health, but their potency to improve treatment of type 2 diabetic (T2D) patients remains poorly characterized. We aimed to evaluate the effect of a combination intervention using EPA + DHA and the insulin-sensitizing drug pioglitazone in overweight/obese T2D patients already treated with metformin. METHODS: In a parallel-group, four-arm, randomized trial, 69 patients (66 % men) were assigned to 24-week-intervention using: (i) corn oil (5 g/day; Placebo), (ii) pioglitazone (15 mg/day; Pio), (iii) EPA + DHA concentrate (5 g/day, containing ~2.8 g EPA + DHA; Omega-3), or (iv) pioglitazone and EPA + DHA concentrate (Pio& Omega-3). Data from 60 patients were used for the final evaluation. At baseline and after intervention, various metabolic markers, adiponectin and cytokines were evaluated in serum using standard procedures, EPA + DHA content in serum phospholipids was evaluated using shotgun lipidomics and mass spectrometry, and hyperinsulinemic-euglycemic clamp and meal test were also performed. Indirect calorimetry was conducted after the intervention. Primary endpoints were changes from baseline in insulin sensitivity evaluated using hyperinsulinemic-euglycemic clamp and in serum triacylglycerol concentrations in fasting state. Secondary endpoints included changes in fasting glycemia and glycated hemoglobin (HbA1c), changes in postprandial glucose, free fatty acid and triacylglycerol concentrations, metabolic flexibility assessed by indirect calorimetry, and inflammatory markers. RESULTS: Omega-3 and Pio& Omega-3 increased EPA + DHA content in serum phospholipids. Pio and Pio& Omega-3 increased body weight and adiponectin levels. Both fasting glycemia and HbA1c were increased by Omega-3, but were unchanged by Pio& Omega-3. Insulin sensitivity was not affected by Omega-3, while it was improved by Pio& Omega-3. Fasting triacylglycerol concentrations and inflammatory markers were not significantly affected by any of the interventions. Lipid metabolism in the meal test and metabolic flexibility were additively improved by Pio& Omega-3. CONCLUSION: Besides preventing a modest negative effect of n-3 fatty acids on glycemic control, the combination of pioglitazone and EPA + DHA can be used to improve lipid metabolism in T2D patients on stable metformin therapy. TRIAL REGISTRATION: EudraCT number 2009-011106-42.